Pelayanan UPT Puskesmas Batang Kulur Kecamatan Sungai Raya Kabupaten Hulu Sungai Selatan - Agus Sya’bani Arlan (Universitas Lambung Mangkurat, 2023)
The research methods used are qualitative methods, data collection techniques, namely: observation, interviews and documentation. The data source was taken through informants totaling 15 people, using data analysis techniques, namely through the stages of reduction, data presentation and drawing conclusions, while the test Data credibility using triangulation.The results showed that the service at the UPT Puskesmas Batang Kulur, Sungai Raya District, Hulu Sungai Selatan Regency, was quite good. Of the 10 subvariables, there are 2 good things, namely: komitmen from management and pengetahu management about quality. Subvariables that show quite good results are found in: the ability to change culture, the ability to build a leadership organization, the value of rewarding and rewarding employees and the conformity between structures. organization. Subvariables that show poor results are found in: sustainablecycling, planning accuracy , adequacy of resources and funds and accuracyof adopting quality management principles into the organization. The factors thathinder the p elayanan di UPT Puskesmas Batang Kulur, Sungai Raya District, Hulu Sungai Selatan Regency, p ertama, lack of discipline of time of Puskesmas officers in providing services to the community, k edua, k urangnya puskesmas employees in providing services to the community, k etiga, weinclude employees in the sustainable cycling. The efforts made to address these inhibiting factors are: pertama, it is hoped that puskesmas officers in providing services to the community so that they can on time, kedua, adding Puskesmas officers in providing services to patients / the community so that the services provided by UPT Puskesmas officers can run well, third, include officers in training sustainable.To improve services at UPT Puskesmas Batang Kulur, Sungai Raya District, Hulu Sungai Selatan Regency, it is recommended to the Head of UPT Puskesmas Batang Kulur to convey to the Head of the Health Office to add service officers at UPT Puskesmas so that services at puskesmas can run well and in accordance with the service process. Meanwhile, Puskesmas employees are expected to improve discipline at work and continue to motivate themselves to support the smooth process of services provided at the Batang Kulur Health Center. Sungai Raya Subdistrict, Hulu Sungai Selatan Regency. For sustainable training programs, it is hoped that the Head of UPT Puskesmas Batang Kulur will provide opportunities for their employees. As for the community, they are encouraged to participate in the smooth service process at the Batang Kulur Health Center. Keywords: Quality of Service; Public Health; Batang Kulur Health Center